2018
DOI: 10.1002/oby.22358
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Operant Responding Under Obesogenic Diet Exposure is not Related to Deficits in Incentive or Hedonic Processes

Abstract: Objective: A growing body of evidence suggests that obesity could result from alterations in reward processing. In rodent models, chronic exposure to an obesogenic diet leads to blunted dopamine signaling and related incentive responding. This study aimed to determine which reward-related behavioral dimensions are actually impacted by obesogenic diet exposure. Methods: Mice were chronically exposed to an obesogenic diet. Incentive and hedonic processes were tested through operant conditioning and licking micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In line with this evidence, humans have shown increased caloric food liking and/or increased hunger ratings in subjects classified as food addicts (Loxton and Tipman, 2017;Ruddock et al, 2017). Mechanistically, it has been proposed that excessive high-energy food consumption seems to negatively modulate a hedonic phenotype in animal models (Kenny, 2011;Barry et al, 2018;Ducrocq et al, 2019), in part, by downregulating the D2 dopamine receptors (Johnson and Kenny, 2010;Winterdahl et al, 2019), and/or reduced dopamine release (Avena and Bocarsly, 2012). In our context, it seems FIGURE 7 | Demethylation inhibits microglia phagocytosis in microglia cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In line with this evidence, humans have shown increased caloric food liking and/or increased hunger ratings in subjects classified as food addicts (Loxton and Tipman, 2017;Ruddock et al, 2017). Mechanistically, it has been proposed that excessive high-energy food consumption seems to negatively modulate a hedonic phenotype in animal models (Kenny, 2011;Barry et al, 2018;Ducrocq et al, 2019), in part, by downregulating the D2 dopamine receptors (Johnson and Kenny, 2010;Winterdahl et al, 2019), and/or reduced dopamine release (Avena and Bocarsly, 2012). In our context, it seems FIGURE 7 | Demethylation inhibits microglia phagocytosis in microglia cells.…”
Section: Discussionsupporting
confidence: 64%
“…Excessive high-energy food consumption seems to modulate positively or negatively a hedonic phenotype in humans and animal models. Several neurotransmitter-related hypotheses were proposed to explain unhealthy eating; for instance, the hypothesis of the reward deficiency states that in the context of high caloric overfeeding or obesity, uncontrolled food intake is activated in order to compensate for a deficient reward effect of food consumption due to failure in the dopaminergic activity (Kenny, 2011;Land and DiLeone, 2012;Barry et al, 2018;Courtney et al, 2018;Gold et al, 2018;van Galen et al, 2018;DiFeliceantonio and Small, 2019;Ducrocq et al, 2019). Under this scenario, impulsiveness for unhealthy eating and caloric overconsumption as a reward is developed (Volkow et al, 2011;Dietrich et al, 2014;Bongers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this resembles the motivational deficit characteristic of SCZ, BP, and MDD that has been shown to originate in part from a distortion of outcome anticipation and representation (Whitton et al, 2015). Impor-tantly, neither the licking microstructures during consumption of the palatable reward (Figure 2F), which allow assessing hedonic reactivity, palatability of the tastant, and post-ingestive feedback mechanisms (Ducrocq et al, 2019), nor spontaneous locomotion were altered in n-3 PUFA-deficient animals (data not shown). Altogether, these data support that the deficits in effort-based tasks in n-3 PUFA-deficient animals are specifically related to impairments in motivational processes with no alteration of hedonic or motoric components.…”
Section: N-3 Pufa Deficiency From Gestation To Adulthood Selectively Alters Pufa Content In Brain Phospholipidsmentioning
confidence: 81%
“…One study showed reduced D1R signalling when a diet high in saturated, but not monounsaturated fats (palm oil vs. olive oil), was administered [101]. Finally, diet-related changes in dopamine synthesis [108], release [59,102,105] and uptake (DAT) [98,99] have been observed.…”
Section: Obesity and Diet-related Dopamine Differencesmentioning
confidence: 99%